An attempt at revealing relationships between morphological characters applied for racial and somatic typology and dermatoglyphics - Gralla, Gertruda; Kmiecik-Rajtko, Helena (Anthropological Review, 1979)
The material for this study comprised young adults (266 males & 336 females) mostly originating from southern Poland whose anthropometric characteristics and descriptive traits suitable for racial typology and somatotyping were observed together with dermatoglyphes on fingers and palms. Detailed analysis of the material has reveled only a few statistically signifficant interdependences between morphology (anthropometry, typology) and dermatoglyphic characters, their pattern being rather unclear. In the majority of comparisons between morphology and dermatoglyphics no significant relations were found. Therefore it can be concluded that relations between classic anthropometric and anthroposcopic characteristics and dermal ridge patterns, if any, are weak.